Effectiveness of smartphone application in teledentistry for enhancing parental knowledge, attitude, and practice (kap) associated with children’s oral health: a systematic review - Anugrah, Pani Matin; Olivia, Marceline; Badruddin, Iwany Amaliah; Adiatman, Melissa; Rahardjo, Anton; Bahar, Armasastra; Darwita, Risqa Rina (Padjadjaran Journal of Dentistry, 2024)
Introduction:  Oral health is essential for children's mental and physical well-being. Caries is one of the most common oral diseases worldwide, especially in children. One of the contributing factors to this disease is parental engagement. Parents play a crucial role in children’s oral health, especially their Knowledge, Attitude, and Practice (KAP). Teledentistry is one of the innovative ways to improve parental KAP due to technological advancements in leveraging the number of smartphones and the internet. Teledentistry could help parents/caregivers obtain education, consultation, diagnosis, and treatment planning about oral health via remote connection without going to dental offices. This engagement of parents/caregivers through teledentistry could build good oral health in children. This review aims to assess the effectiveness of smartphone applications for teledentistry in parental KAP related to children's oral health. Methods: This review followed PRISMA guidelines. We searched the articles in five databases (PubMed, EBSCOhost via Medline, Embase, ProQuest, and Scopus) using specific keywords and a PICO framework from January 2018 to December 2023. Two reviewers independently selected the articles based on inclusion and exclusion criteria. The selected articles were extracted and assessed for risk of bias using MMAT tool. Results: Of the 1529 articles initially identified, 14 met the inclusion criteria. All smartphone application reviewed were designed for parents/caregivers and integrated with teledentistry; however, only two applications incorporated with artificial intelligence. All application showed good assessment through application tests using SUS (3 articles), JN’s principles (1 article), Net Promotor Score (1 article), MARS (1 article), TAM (1 articles), and sensitivity and specificity tests (2 articles). Parental/caregiver engagement was assessed through their Knowledge, Attitude, and Practice (KAP). This has impacted the children’s oral health by improving both the plaque and gingival index. Conclusion: Smartphone applications for teledentistry effectively increase the engagement and KAP of the parents/caregivers, significantly improving the oral health status of the children.